Effect of l-Arginine in One Patient with Peroxisome Biogenesis Disorder due to PEX12 Deficiency - Sorlin, Arthur; Briand, Gilbert; Cheillan, David; Wiedemann, Arnaud; Montaut-Verient, Bettina; Schmitt, Emmanuelle; Feillet, François (Neuropediatrics, 2016)
Peroxisome biogenesis disorders (PBD) are a heterogeneous group of disorders due to PEX genes mutations, with a broad clinical spectrum comprising severe neonatal disease to mild presentation. Recently, Berendse et al reported an improvement of peroxisomal functions with l-arginine supplementation in fibroblasts with specific mutations of PEX1, PEX6, and PEX12. We report the first treatment by l-arginine in a patient homozygous for the specific PEX12 mutation shown to be l-arginine responsive in fibroblasts. We described the effect of l-arginine on biochemical (decrease of some plasma peroxisomal parameters) and neurophysiological (improvement of deafness) parameters. Some subjective clinical effects have also been observed (no more sialorrhea, behavior improvement). More studies are needed to assess the efficacy of l-arginine in some PBD patients with specific mutations.
Keywords: pediatrics; metabolism; l-arginine